THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK LIFE BALANCE WORK MOTIVATION AND ITS IMPLICATIONS ON TEACHER PERFORMANCE AT THE TZU CHI LOVE SCHOOL TEACHER CENGKARENG, WEST JAKARTA - Yoga Mahardika, Ghana; M. Havidz Aima; Ikramina Larasati H. H (Dinasti Publisher, 2022)
This study aims to analyze the effect of organizational culture and work-life balance on work motivation and their impact on teacher performance. Determining the number of samples using the Slovin formula from a population of 143 obtained as many as 128 samples. This research is a quantitative research using the Structural Equation Model-Partial Least Square (SEM-PLS) research analysis method. The research findings show: (1) organizational culture has a significant positive effect on work motivation and teacher performance; (2) Work life balance has no significant effect on work motivation, but has a positive and significant effect on teacher performance; and (3) work motivation has no significant effect on teacher performance.